An exploratory study for the perception and attitude of internship program by students of speech and hearing - A., Srividya; Thontadarya, Suresh; Babu, Praveena (International Journal Of Community Medicine And Public Health, 2023)
Background: The attitude and opinion of internship experience as reported by students can be a useful data for effective monitoring of any academic program. Such methods are common practice worldwide, e.g., ASHA publishes survey reports annually. The present project was aimed at evaluating the perception and attitude of students of the internship program of speech and hearing sciences at the graduate level of DrSRCISH. Methods: The data was from 75 intern students posted at different rehabilitation, diagnostic and school setups. The study used a self-administered questionnaire in digital form (Google form) which had 22 questions in multiple choice or true/false statements. The questionnaire had three sections-demographic, experiences of the internship, and shortcomings in the internship. Results: Completed forms were received from the 31 out of 75 subjects. The forms were available for internees for a period of one month. Return rate was 41%. Current internship is able to provide diversity of internship training. Institution, special schools and Hospitals were the highest choices with 23%. The results support the principles of internship as formulated by RCI and ASHA. i.e. internship is necessary for clinical training programs. Supervision received, infrastructure, case load and working hours received favourable rating. The least favourite part of internship postings was logistics or travel concerns. Conclusions: The results of the data depict the effectiveness of the internship program on the professional - personal growth and skills of the students of speech and hearing sciences. Multidisciplinary working atmosphere, learning new skills were the strength of the program.